Porcine Torovirus (PToV)—A Brief Review of Etiology, Diagnostic Assays and Current Epidemiology - Hu, Zhang-Min; Yang, Yong-Le; Xu, Ling-Dong; Wang, Bin; Qin, Pan; Huang, Yao-Wei (Frontiers in Veterinary Science, 2019)
Porcine torovirus (PToV) is a potential enteric swine pathogen, found at especially high rates in piglets with diarrhea. It was first reported in the Netherlands in 1998 and has emerged in many countries around the world. Infections are generally asymptomatic and have not directly caused large economic losses, though co-infections with other swine pathogens and intertype recombination may lead to unpredictable outcomes. This review introduces progress in PToV research regarding its discovery, relationship with other Toroviruses, virion morphological characteristics, genetic structure and variation, recent epidemiology, diagnostic methods, and possibilities for future research.